Dislocalism : The Crisis fo Globalization and the Remobilizing of Americanism - Chandra, Sarika, 1969- (Book collections on Project MUSE., 2011)
"Taking her title from a new theoretical concept at the heart of this critique, Sarika Chandra argues that the historically dominant position of the United States in the global order takes on a uniquely urgent and problematic form: globalization is experienced not only as external to the American "nation of nations" but also as something internal to it. Through close study of four discrete intellectual/cultural arenas from the 1980s to the present--management theory, the literature of immigration, travel writing, and narratives of the culinary exotic--Chandra further argues that an Americanized imperative to globalize results in a repositioning of the local to maintain national and institutional boundaries ... By mapping out the deeper, often hidden discursive ambiguities and historical specificities of an Americanized globalization, Dislocalism effectively redefines and re-orients the fields of American literary and cultural studies"--Publisher's description